Age-related variation in body weight and morphometric traits of local pigs in the northern coastal area of North Insana District, Timor Tengah Utara Regency, Indonesia - Yuliana Kolo; Maria S. Pasi; Leonardus F. Obe; Veronika Y. Beyleto (Fakultas Peternakan Universitas Papua, 2026)
This study evaluated the zoometric characteristics of local pigs raised in the northern coastal area of North Insana District, Timor Tengah Utara Regency, across different age groups. A total of 85 pigs were classified into piglets (1–4 months, n=24), young pigs (5–12 months, n=21), and adults (>12 months, n=40). Body weight, body length, chest girth, shoulder height, ear length, head length, hind leg length, and tail length were measured directly in the field and analysed descriptively. All measured traits increased with age, with the highest values consistently recorded in adult pigs. Mean body weight increased from 4.34 ± 1.62 kg in piglets to 47.95 ± 14.91 kg in young pigs and 97.37 ± 4.39 kg in adults. Similar age-related increases were observed for all linear body measurements. Coefficients of variation were generally higher in piglets and young pigs and lower in adults, indicating greater growth heterogeneity during early development and greater uniformity after maturity. These findings show that zoometric traits are useful indicators of growth and body development in local pigs under smallholder coastal conditions. The study provides baseline morphometric information to support phenotypic characterisation, breeding stock selection, and conservation of local pig genetic resources.